Penerapan model course review horray untuk meningkatkan sikap kerjasama dalam muatan pembelajaran IPS pada peserta didik kelas v sekolah dasar - Hikmah, Isna Miftakhul; Sukarno, Sukarno; Chumdari, Chumdari (Didaktika Dwija Indria, 2021)
The goal of this research is to improve the attitude of cooperation through the application of the Course Review Horray learning model in social studies. The subjects of this study were teachers and 30 students from fifth-grade public elementary school Mangkuyudan Surakarta for the 2019/2020 school year. This research is a classroom action research that has three cycles with two meetings each cycle. The data collected were interviews, observation of students’ cooperative attitudes, assessment among students, and documentation. Data validity of this study using technical triangulation and source triangulation. The data analysis technique used is Miles & Huberman's interactive descriptive analysis model.  In the first cycle, students who got the very good cooperation category reached 13%, the second cycle reached 50%, while the third cycle reached 83% in classical completeness. The conclusion of this research is the cooperative attitude of a fifth-grade public elementary school Mangkuyudan Surakarta academic year 2019/2020 increases through the application of Course Review Horray learning models.